Matahara dan Patahara: Tantangan Hak Cuti Mengurus Anak Dalam Budaya Korporasi Jepang - Rizky Aurelia Putri Dehars (IZUMI, 2023)
This research discusses about maternity harassment and paternity harasement that is happening in Japanese work environment which linked to Japan;s declining population. The writer used qualitative method and literature study from Japanese ministries websites, Japanese and international news article,as well as local and international journal. From teh data that has been gathered and analyzed, it can be concluded that maternity harassment and paternity harassment was caused by Japanese corporations long-hours work environment. Those who can’t comply to the rules were seen as incompetent and jeopardized the company. However, this mistreatment and the Japanese work environment were also causing Japanes population to decline. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor